SHAPING PRODUCTIVE CULTURAL CONTENT FOR EFL MATERIALS IN CONTEMPORARY RUSSIAN ELT PRACTICES - Peter J. Mitchell; Andrei G. Shilnov (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2019)
The article attempts to develop guidelines for the inclusion / non-inclusion of specific cultural content into EFL materials for contemporary ELT practices in Russia. Cultural circumstances surrounding the ELT practices in today's Russia and their connection with the past are analyzed. Some approaches to the usage of materials are considered, with examples of specific published and online materials provided. An exemplar of a lesson plan on a thought-provoking topic with sample activities and materials is presented based on the approaches and principles described. A conclusion is made on the necessity of offering teacher training on shaping productive cultural content for EFL materials that are appropriate to the teaching context. Keywords: English language teaching (ELT), English as a foreign language (EFL), textbook, cultural content.